Red Dwarf. VI [videorecording (DVD)] - Grant, Rob (Robert Ray); Naylor, Doug; De Emmony, Andy; Judd, Justin; Barrie, Chris, 1960-; Charles, Craig, 1964-; John-Jules, Danny; Llewellyn, Robert, 1956- (BBC Video ; Distributed by Warner Home Video, 2005)
The mining ship Red Dwarf is lost in deep space and Lister can't remember where he parked it! Chasing their mother ship leads them through simulant hunting zones, hostile GELF space, and even a Wild West reality.